Strategi Konten Kreatif Dalam Membentuk Citra Merek Di Media Sosial: (Studi Kasus Pada Usaha Konten Kreatif Yelo Studio) - Fani, Mukhammad As Alukal Huda Mei; Daulay, Aqwa Naser; Harianto, Budi (Jayapangus Press, 2024)
This study examines creative content strategies in shaping brand image on social media, focusing on PT. Yelo Solusi Kreativa and Rio Purba as the founder. The background of this research is the rapid development of information technology, which has made social media an essential platform for companies to expand their marketing reach and strengthen relationships with consumers. The study aims to understand the effective and strategic application of creative content in shaping brand image. The research method uses a descriptive qualitative approach with content analysis. Primary data were obtained through in-depth interviews, and secondary data came from books, journals, the internet, and other relevant sources. The research subjects were selected through purposive sampling, involving individuals with knowledge and experience related to the topic. Data collection techniques included interviews, observation, and document analysis. The analysis was conducted systematically and objectively to identify relevant characteristics. The results showed that Rio Purba uses personal social media as a communication and information tool. Social media content was categorized into four types: collaboration, entertainment, information, and education. From June 2023 to March 2024, 45 pieces of content were collected and analyzed. Collaborative content played a role in building personal branding and increasing followers. Entertainment and educational content helped maintain audience engagement. The study concludes by emphasizing the importance of creative content strategies in shaping a strong and relevant brand image on social media, which not only enhances visibility but also strengthens relationships with consumers.